The employment experiences of graduates with disabilities in South Africa : challenges and resilience - Ubisi, Lindokuhle Mdeyi (My University, 2017)
The career trajectory for persons with disabilities (PWDs) has largely been associated with decline and stagnation. Resilience and positive attributes have not been investigated related to graduates with disabilities (GWDs) successfully entering, adjusting to and further developing within the work environment. The aim of this study was to report on challenges, resilience and positive attributes amongst GWDs as a positive contributing factor to employment practices as well as policy. A participant sample of 6 employed GWDs (working age 26-45; 4 males and 2 females; 3 Black, 2 White and 1 Coloured) were individually interviewed. The participants’ disabilities consisted mainly of physical, hearing and visual impairments. The data was analysed using thematic and discourse analysis. Results show that despite the negative experiences encountered within the social and work environment, participants demonstrated resilience within their narratives and decision-making processes. A self-developed conceptual model of resilience and positive attributes was thus proposed to track this resilience. However, the resilience observed amongst participants did not fully reflect the existing definitions and theoretical frameworks around resilience. Critically re-examining these existing definitions and the theoretical framework showed new meanings can be derived with implications for policy and intervention. The fact that the majority of participants did not show awareness of or ownership of their resilience shows a missing key element – that they are not only making use of it, but they also do not even appear to realise its importance.
A submitted thesis of Masters of Art in Social and Psychological Research, University of the Witwatersrand, Faculty of Humanities, School of Human and Community Development, 2017
Keywords: People with disabilities--Employment--South Africa; People with disabilities--Education (Higher)--South Africa; College graduates--Employment--South Africa